Adolescents', parents' and peers' mathematics anxiety, attitudes toward mathematics and mathematics achievement - Chong, Yung Yung (Universiti Malaysia Sarawak, UNIMAS, 2014)
The significance of attitudes toward mathematics in mathematics teaching and learning has been highlighted in the literature, but with less emphasis as compared to mathematics anxiety. Attitudes toward mathematics and mathematics anxiety are two essential variables in determining students’ mathematics performances and achievements in mathematics. Moreover, there were less research that studied the correlation between students’ own mathematics anxiety and attitudes toward mathematics. Therefore, the main focus of this research is to investigate the correlation between mathematics anxiety, attitudes toward mathematics, and mathematics achievements, their relationships to adolescents’ perceptions of parents’ and peers’ mathematics anxiety and attitudes toward mathematics, and gender differences in adolescents’ mathematics anxiety, attitudes toward mathematics, and mathematics achievement. This correlational and comparative research design study involved 480 adolescents Form Four students from six rural secondary schools. The focus on middle adolescents of Form Four Students, as the samples of this study was due to the reason that middle adolescents represent students who are starting to face more difficulties as the level of complexity and mathematics abstraction increased as compared to lower secondary. Adolescents’ perception of parents’ and peers’ were investigated as possible influence variables of adolescents’ mathematics anxiety level, positive or negative attitudes toward mathematics and level of mathematics achievements. The main instrument of this study was a questionnaire which composed of the Mathematics Anxiety Rating Scale-Revised (MARS-R) and revised model of Attitude toward Mathematics Inventory (ATMI). Results indicated positive relationships between adolescents’ mathematics anxiety with their perceptions of their parents’ mathematics anxiety (r = 0.534, p < 0.005), and their peers’ mathematics anxiety (r = 0.625, p < 0.005); between adolescents’ attitudes toward mathematics and their perceptions of their parents’ attitudes toward mathematics (r = 0.799, p < 0.005) and their peers’ attitudes toward mathematics (r = 0.814, p < 0.005); and relationships between adolescents’ perceptions of their own mathematics achievement with their own attitudes toward mathematics (r = 0.524, p < 0.005), perceptions of their parents’ attitudes toward mathematics (r = 0.382, p < 0.005), and perceptions of their peers’ attitudes toward mathematics (r = 0.415, p < 0.005). The findings of present study also found negative relationships between adolescents’ perceptions of own mathematics achievements with their own mathematics anxiety level (r = - 0.303, p < 0.005), with perceptions of their parents’ mathematics anxiety (r = - 0.252, p < 0.005), and perceptions of peers’ mathematics anxiety (r = - 0.201, p < 0.005); and also negative relationships between adolescents’ mathematics anxiety and attitudes toward mathematics (r = - ix